Acute Portal Vein Thrombosis Diagnosed with Point-of-care Ultrasonography - Wells, Daniel (Clin Pract Cases Emerg Med, 2017)
Abdominal pain is the most common presenting complaint to the emergency department (ED);1 however, acute portal vein thrombosis is an uncommon cause of abdominal pain. In the following case report, we present a patient who presented to the ED with symptoms of gastroenteritis but was ultimately diagnosed with acute portal vein thrombosis by point-of-care ultrasound (POCUS).